Usage of JSTOR Database Among Research Scholars in the Faculty of Social Science, Aligarh Muslim University - Ansari, Nahav Alam; Raza, M Masoom (DESIDOC Journal of Library & Information Technology, 2018)
The study set out to examine the researchers’ perception towards the use JSTOR database and to explore the reasons not to use JSTOR database. The present study carried out using simple random sampling technique. The major purpose of researchers to use JSTOR was research work and article title was the most common searching techniques in simple search category. In advanced search technique field search was most common search technique followed by phrase search. Almost, all respondents found satisfied with the service of JSTOR and none was found dissatisfied/partially satisfied. On the basis of findings, it is recommended that the use of JSTOR database can be maximised, if researchers have frequent literacy programs.